Remittances and Agricultural Technical Efficiency in Africa: Panel Data Analysis - Kidanemariam Gebregziabher; Daniel Makina; Muuz Hadush (Migration Letters, 2023)
The paper examines the impact of international remittances on agricultural technical efficiency across 34 African countries and 31 years panel data. To estimate the stochastic production frontier three classical production inputs and eleven technical efficiency (excluding time dummies) variables are included in our analysis. All inputs variables found to be highly significant. While the covariates in the inefficiency estimation, such as, mobile and private credit found to be against our expectations, and the rest were consistent and highly significant. Especially, the variable of our interest, international remittances tend to show a U-shape, with first order variable being positive and negative in the second order (both significant at 1% level). Regional as well as time dummies are also very consistent and most of significant. Hence, to improve the utilization of remittance and channel the resource to productive purpose more governmental effort in educating remittance recipients seems necessary.